Beyond Compliance: Quantifying the Impact of Occupational Safety and Health on Worker Performance in High-Rise Construction - Ria Riskiyah, Indah; Utoyo, Suselo; Sumardi, Sumardi; Jatu Noviarsita, Radhia; Cahyani, Eri (Asian Journal Science and Engineering, 2025)
The construction industry is globally recognized for its high occupational risks, making the implementation of robust Occupational Safety and Health (OSH) programs a critical concern. While the importance of OSH is undisputed, its direct, quantifiable impact on worker performance requires continuous empirical validation. This study aims to analyze the influence of occupational safety and occupational health practices on the performance of workers in a high-rise building project in Surabaya, Indonesia. Utilizing a quantitative approach, data were collected from 63 project personnel via a structured questionnaire. The data were analyzed using multiple linear regression. The results confirm a significant and positive relationship, with OSH practices collectively explaining 44.2% of the variance in worker performance (Adjusted R² = 0.442). A partial analysis of the regression coefficients revealed that occupational safety (β = 0.453) exerts a more dominant influence on performance than occupational health (β = 0.341). This study provides quantitative evidence that OSH programs are not merely a compliance requirement but a direct investment in operational productivity, with tangible safety measures being the primary driver of enhanced worker performance.